1995
DOI: 10.1108/09588689510104060
|View full text |Cite
|
Sign up to set email alerts
|

Property cycles in the UK: an empirical investigation of the stylized facts

Abstract: Applies the methodology adopted in contemporary business cycle research on establishing the stylized facts of aggregate output fluctuations, in the context of the office, industrial and retail building cycle. The objective of the study is to identify the degree to which cyclical regularities, which are in conformity with theoretical modelling, are identified across property sectors. Undertakes a statistical analysis of the cyclical properties of certain variables in relation to the building cycle in the respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…Over time, cyclical understanding matured. Rather than merely a reflection of human transit, later cyclical investigations saw property market fluctuations in their wider business/economic context (RICS, 1994;Barras, 2009;Barras and Ferguson, 1985;Grebler and Burns, 1982;Wheaton, 1987;Barras, 1994;McGough and Tsolacos, 1995). A seminal study commissioned by the Royal Institution of Chartered Surveyors (RICS, 1994) jointly with the University of Aberdeen and the Investment Property Databank (IPD) confirmed significant interplay between property and economic cycles.…”
Section: Literature Review Historical Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Over time, cyclical understanding matured. Rather than merely a reflection of human transit, later cyclical investigations saw property market fluctuations in their wider business/economic context (RICS, 1994;Barras, 2009;Barras and Ferguson, 1985;Grebler and Burns, 1982;Wheaton, 1987;Barras, 1994;McGough and Tsolacos, 1995). A seminal study commissioned by the Royal Institution of Chartered Surveyors (RICS, 1994) jointly with the University of Aberdeen and the Investment Property Databank (IPD) confirmed significant interplay between property and economic cycles.…”
Section: Literature Review Historical Perspectivementioning
confidence: 99%
“…Retail property in particular seems to be synchronised with changes in GDP, consumer expenditure and non-food retail sales. McGough and Tsolacos (1995) examined amplitude, persistence, pro-cyclicality and counter-cyclicality of the UK commercial property cycles. Using the HP technique, they smoothed the selected series.…”
Section: Jpif 354mentioning
confidence: 99%
“…Property professionals and scholars blamed inaccurate data, its analysis and interpretation, and anticipated that things will improve next time (rIcS 1994; Barras 2005). consequently, it prompted a number of important publications on the subject, including Barras (1994), rIcS (1994, grenadier (1995), Mcgough and tsolacos (1995), and renaud (1995). Barras (1987) time-series of 5 sectorsprivate industrial, commercial and house-building, and public house-building and other public building time-series analysis ; time-series modelling; Spectral analysis; turning point analysis 20-30 years 'urban development cycles'; Interconnection between 5 year, 10 year, and 20 year cycles; Suggestions for policy making Wheaton (1987) time-series (construction, completions, office employment, absorption, vacancy rate)…”
Section: Post 1990s Property Crash Studiesmentioning
confidence: 99%
“…Moreover, it has also been demonstrated that 'different cyclical forces are at work in the occupier market, the development industry and the investment market, sometimes opposing and sometimes reinforcing each other ' (ibid., p. 195). therefore, as Barras stated, a better knowledge of ; turning point analysis; Visual data analysis; correlation analysis; time-series simulation; timeseries desmoothing; filtering (HP technique); Spectral analysis; Multivariate time-series regression with variable additions/deletion; long-run cointegration 4-9 years cycles; correlation with the economy; Strong cyclical pattern; long-run analysis adds little to the ability to understand or predict the market Mcgough and tsolacos (1995) gDP; employment; consumer expenditure; Industry output; Interest rates time-series analysis (1980)(1981)(1982)(1983)(1984)(1985)(1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994); Statistical analysis (amplitudestandard deviation, persistencefirst order autocorrelation, procyclicality and countercyclicalitycross-correlation) correlation between gDP, manufacturing and business output and the office and industrial property; and between gDP, consumer expenditure and non-food retail sales and retail property; establishment of stylized facts the interaction of these underlying forces leads to a greater understanding of the property cycle.…”
Section: Post 1990s Property Crash Studiesmentioning
confidence: 99%
“…So far, most of the modern research into UK property cycles has been limited to the commercial property market sector (McGough and Tsolacos, 1995;RICS, 1994RICS, , 1999Barras, 2005;Ball and Grilli, 1997;Scott and Judge, 2000;Krystalogianni et al, 2004). Bracke (2013), among the few studies that concentrates on housing cycles, analysed data for 19 countries, including the UK.…”
Section: Overview Of the Literaturementioning
confidence: 99%